The influence of body image on surgical decisions in adolescent idiopathic scoliosis patients - Paulo Alvim Borges; José Thomé de Carvalho Neto; Olavo Biraghi Letaif; Raphael Martus Marcon; Alexandre Fogaça Cristante (Clinics)
OBJECTIVES: The objective of this study was to evaluate whether the severity of deformities in patients with adolescent idiopathic scoliosis contributes to patients’ decision regarding whether to undergo an operation. METHODS: We evaluated body image factors in adolescent idiopathic scoliosis patients. We evaluated the magnitude of the main scoliotic curve, gibbosity (magnitude and location), shoulder height asymmetry and patient’s age. We analyzed the correlation of these data with the number of years the patient was willing to trade for surgery, as measured by the time-trade-off method. RESULTS: A total of 52 patients were studied. We did not find a correlation between any of the parameters that were studied and the number of years that the patient would trade for the surgery. CONCLUSIONS: The magnitude of body deformities in patients with adolescent idiopathic scoliosis does not interfere with the decision to undertake surgical treatment.